The Utilization of Spent Oyster Mushroom Substrates Into Compost and Its Effect on the Growth of Indian Mustard (Brassica juncea (L.) Czern.) in the Screenhouse - Priadi, D.; Saskiawan, I. (International Journal of Agricultural Technology, 2018)
Spent mushroom substrate is a byproduct of mushroom industries that created various environmental problems.The utilize spent oyster mushroom substrate which mainly contains sawdust to be made as organic fertilizer was investigated. Fresh sawdust, sawdust from the spent oyster mushroom substrate and cow manure was composted and its effects on the growth of Indian mustard (Brassica juncea) were determined. The composition of compost substrate was sawdust (L1) or spent oyster mushroom substrate (L2) in combination with cow manure ratio of 100% (P1), 75% (P2), 50% (P3), 25% (P4), and 0% (P5). Composting parameters were pH, temperature, water content, organic C, total N, P, K content, and C/N ratio, while the plant growth parameter was the plant height, total leaves, and wet weight per plant. The study showed that the best produced compost was from the combination of sawdust or spent oyster mushroom substrate and cow manure (L1P2 and L2P2). It is suggested that a problem for organic waste utilization into compost can be solved.The highest plant height, total leaves, and wet weight per plant of Indian mustard were obtained from the plant fertilized with the compost from cow manure alone, which were not significantly different with that 25% sawdust and 75% cow manure (L1P2) or 25% spent oyster mushroom substrate and 75% cow manure (L2P2).